Annual Convention of the European Platform Against Poverty and Social Exclusion, Brussels, 5-7 december 2012 - team, Editorial (Ревија за социјална политика/Journal of Social Policy, 2013)
The European Platform Against Poverty and Social Exclusion is one of the forerunning initiatives of the Europe 2020 Strategy for smart, sustainable and inclusive growth. It was created in 2010 and establishes the activities for attaining the EU target for reducing poverty and social exclusion by at least 20 million till the year 2020. The Second Convention of the European Platform against poverty and social exclusion was organized 5-7 Decem - ber 2012, in Brussels. The objective of the Convention was to reflect on the progress made towards achieving the goal of poverty re duction, also serving as a Forum for consultations for the coming Social Investment Packаge.